Obesogenic and diabetic effects of CD44 in mice are sexually dimorphic and dependent on genetic background - VerHagye, Melissa; Albright, Jody; Barron, Keri; Kim, Myung Suk; Bennett, Brian (BioMed Central, 2022)
Introduction CD44 is a candidate gene for obesity and diabetes development and may be a critical mediator of a systemic inflammation associated with obesity and diabetes. Methods We investigated the relationship of CD44 with obesity in CD44-deficient mice challenged with a high-fat diet. Results In mice fed a diet high in fat, cholesterol, and sucrose for 12 weeks fat mass accumulation was reduced in CD44-deficient mice bred onto both a C57BL/6J and the naturally TLR deficient C3H/HeJ background. Reduced fat mass could not be attributed to lower food intake or an increase in energy expenditure as measured by indirect calorimetry. However, we observed a 40-60% lower mRNA expression of the inflammation markers, F4/80, CD11b, TNF-alpha, and CD14, in adipose tissue of CD44-deficient mice on the C57BL/6J background but not the C3H/HeJ background, perhaps indicating that alternative factors may be affecting adiposity in this model. Measures of hepatic steatosis and insulin sensitivity were improved in CD44-deficient mice on a C57BL/6J but not in the C3H/HeJ mice. These results were highly sexually dimorphic as there were no detectable effects of CD44 inactivation in female mice on a C57BL/6 J or C3H/HeJ background. Conclusion CD44 was associated with adiposity, liver fat, and glucose in male mice. However, the effects of CD44 on obesity may be independent of TLR4 signaling.